2021
DOI: 10.12669/pjms.37.6-wit.4886
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of left ventricular diastolic function of patients with coronary heart disease by ultrasound images on bilateral filtering image noise reduction algorithm combined with electrocardiogram

Abstract: Objective: To explore the evaluation of left ventricular diastolic function (LVDF) in patients with coronary heart disease (CHD) using ultrasound images (UI) combined with electrocardiogram (ECG) on bilateral filtering image noise reduction algorithm (BFINRA). Methods: A BFINRA was constructed, and 60 subjects who were investigated were divided into a control group (CG) from June 2019 to November 2019 in Taizhou People’s Hospital, a myocardial infarction group (MIG), and an angina pectoris group (APG). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…It was shown from the results that the PSNR of the bilateral filtering algorithm (800 dB) was greatly higher than that of the wavelet threshold denoising (321 dB) and the nonlocal mean filtering algorithm (455 dB). is was consistent with the findings of Li [35]. e segmentation accuracy of the improved region growing method/the improved fuzzy spatial clustering algorithm (96.21% and 97.22%) was higher than that of the unimproved ones (82.11% and 79.99%).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It was shown from the results that the PSNR of the bilateral filtering algorithm (800 dB) was greatly higher than that of the wavelet threshold denoising (321 dB) and the nonlocal mean filtering algorithm (455 dB). is was consistent with the findings of Li [35]. e segmentation accuracy of the improved region growing method/the improved fuzzy spatial clustering algorithm (96.21% and 97.22%) was higher than that of the unimproved ones (82.11% and 79.99%).…”
Section: Discussionsupporting
confidence: 91%
“…It was suggested that the combination of automatic threshold and boundary tracking could optimize the region growing algorithm, and the automatic peak detection method could improve the segmentation effect of the fuzzy spatial clustering algorithm. Khodaverdi et al [35] came up with an automatic threshold and boundary tracking algorithm that could distinguish the target from the background, which was more conducive to image segmentation. Chen and Maharatna [36] proposed that the peak automatic detection method could improve the retrieval efficiency of the clustering centers in the fuzzy spatial clustering algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…As such, numerous studies have proposed that PtfV1 signifies an increase in volume or pressure in the left atrium, decreased inter-atrial conduction, and fibrosis of the left ventricle. 6 , 8 , 16 , 17 These indications may predict the potential risk of MACEs. 15 , 18 …”
Section: Discussionmentioning
confidence: 99%
“…As such, numerous studies have proposed that PtfV1 signifies an increase in volume or pressure in the left atrium, decreased inter-atrial conduction, and fibrosis of the left ventricle. 6,8,16,17 These indications may predict the potential risk of MACEs. 15,18 Research indicates that an abnormal PtfV1 value may be linked to left ventricular diastolic dysfunction resulting from infarcted myocardium, even prior to the onset of heart failure symptoms and left ventricular systolic dysfunction.…”
Section: Discussionmentioning
confidence: 99%